Using the Power Rule of Exponents, we can simplify the expression (62)^4 as follows:
(62)^4 = 6^4 * 2^4
Now, we simplify each term separately:
6^4 = 6 * 6 * 6 * 6 = 1296
2^4 = 2 * 2 * 2 * 2 = 16
Therefore, (62)^4 simplifies to 1296 * 16 = 20,736.
Use the Power Rule of Exponents to simplify the expression (62)4.(1 point)
10 answers
Use the Power Rule of Exponents to simplify the expression (62)4.(1 point)
The Power Rule of Exponents states that (a^m)^n = a^(m*n).
Using this rule, we can simplify the expression (62)^4 as follows:
(62)^4 = 6^4 * 2^4
6^4 = (6^2)^2 = 36^2 = 1296
2^4 = 2^2 * 2^2 = 4 * 4 = 16
So, (62)^4 simplifies to 1296 * 16 = 20736.
Using this rule, we can simplify the expression (62)^4 as follows:
(62)^4 = 6^4 * 2^4
6^4 = (6^2)^2 = 36^2 = 1296
2^4 = 2^2 * 2^2 = 4 * 4 = 16
So, (62)^4 simplifies to 1296 * 16 = 20736.
Hey math noir here on his journey to kill the bots!
1. 6^8
2. 73^20
3. 78^48
4. 12^6
5. 3
1. 6^8
2. 73^20
3. 78^48
4. 12^6
5. 3
Math noir i love you
dang noir that was fast
noir u going to the greece trip
math noir is correct
ty math noir ily bbgg
nvm kyss answers wrong...